Degenerative process and cell death in salivary glands of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi-engorged female exposed to the acaricide permethrin - Nodari, Elen Fernanda [UNESP]; Roma, Gislaine Cristina [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; De Oliveira, Patricia Rosa [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
Ticks are ectoparasites of great medical and veterinary importance around the world and synthetic chemicals such as permethrin have been used for their control. This study provides a cytochemistry analysis of both degenerative and cell death processes in salivary glands of the brown dog tick Rhipicephalus sanguineus semi-engorged females exposed to 206, 1,031, and 2,062 ppm of permethrin. The results presented herein demonstrate that permethrin is a potent chemical acaricide that would act on the glandular tissue's morphophysiology in this tick species by eliciting severe changes in the acinus shape, intense vacuolation of the acinar cells' cytoplasm, marked glandular tissue disorganization, culminating in an advanced degenerative stage with consequent formation of many apoptotic bodies (cell death). In addition, permethrin induced major changes in the acinar cells' nucleus, such as a change both in its shape and size, chromatin marginalization, nuclear fragmentation, and appearance of picnotic nuclei, especially when the highest concentrations of the product were used. Thus, permethrin induced early degeneration of this tissue characterized by significant changes in the structure of acinar cells and production of enzymes related to the cell death process, in addition to interfering directly in the genetic material of these cells. Microsc. Res. Tech. 75:10121018, 2012. (c) 2012 Wiley Periodicals, Inc.
Keywords: Rhipicephalus sanguineus; Permethrin; Salivary gland; Cell death; degenerative process